PENGARUH PENGGUNAAN PUZZLE TERHADAP PEMAHAMAN KONSEP SISWA UPT SD NEGERI 010 SIABU - Muhayat, Badrul; Hidayat, Adityawarman; Wahyuni, Molli; Fadhilaturrahmi, Fadhilaturrahmi; Yandri Kusuma, Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by a problem encountered in the fifth grade of siabu state elementary school 010. Based on the results of written tests administered to fifth-grade students at siabu state elementary school 010 and interviews with the teacher, mrs. Elfitria, s.pd., it was found that the learning process had not utilized learning media optimally to support mathematics learning. So far, the learning process had been limited to explaining the material on the board, providing examples, and giving assignments. The learning process is quite good, but the use of learning media in mathematics is not yet optimal. This study aims to determine the efforts to describe the effect of using puzzles on students' conceptual understanding at the upt sd negeri 010 siabu. This study was conducted at the upt sd negeri 010 siabu in the 2025 academic year. The research method used was a quasi-experimental design in the form of a one-group pretest-posttest. Where the sample consisted of an experimental class of 21 students and a control class of 21 students. Data analysis with hypothesis testing in this study was carried out using a two-way independent t-test formula (independent sample t-test). The results of this study obtained a significance value (sig) in the independent test table of 0.000 <0.050, so it can be concluded that there is a significant difference in conceptual understanding between students who learn using puzzles and students who learn using the ctl method. Thus, the use of puzzle learning media has a significant effect on improving students' conceptual understanding compared to ctl learning.